Epitaxial hetero-structure of CdSe/TiO2 nanotube arrays with PEDOT as hole transfer layer for photoelectrochemical hydrogen evolution - Chong, Baohe; Zhu, Wen; Hou, Xianghui (Royal Society of Chemistry, 2017)
The photocatalytic decomposition of water is believed to be able to help mitigate the crisis of fossil fuel depletion. However, the photocatalytic hydrogen production remains challenge to obtain high and stable photoconversion efficiency. Here we report an epitaxial hetero-structure of CdSe/TiO2 nanotube arrays as efficient photo-anodes via simple room-temperature, low-cost electrochemical deposition. With the help of the similar d spacing with TiO2, CdSe sensitization layer is epitaxially grown on the tube wall of the TiO2 nanotubes, resulting in an ideal coherent grain boundary and single crystal growth. The resultant photo-anode produces 30% more photocurrent than those samples without coherent grain boundary. Notably, the especial epitaxial hetero-structure is beneficial to decrease the recombination site and accelerate the separation of photogenerated electron-hole pairs. Furthermore, an ultrathin PEDOT surface layer was developed on the epitaxial hetero-structure of CdSe/TiO2 nano-tube arrays in which it functions as both a physical passivation barrier and a hole transfer layer. As a result, significantly enhanced photocurrent density and substantially better stability have been achieved. This methodology may be providing a new pathway of epitaxial growth for preparing the heterogeneous junction materials which have similar d spacing.